Cele i organizacja zakładów karnych w I Rzeczypospolitej - Bieda, Justyna (Acta Universitatis Lodziensis. Folia Historica, 2015)
The features of prisons in old Poland, their role and the organization were changing along with the evolution of views on the aims and goals of punishment in the criminal justice system. Quite different is the picture when punishment is to have the rehabilitation effect and another if the basic premise of penal policy is the principle of deterrence, and not to amend the morality of the criminals (that was the situation in Poland until the 18th century). The imprisonment could be conducted in five different ways. The choice of prison was performer on the basis of the type of crime committed, but was the condition of the convict was also of some importance. At as early as in the 12–13th centuries there appeared prisons for people of lower states, to which burghers and peasants were sent. Initially, they acted as a preventive measure only. In the Middle Ages an upper tower, used mainly in relation to the nobility, was developed. It was an institution according to which the penance took place in decent, almost home-like, conditions. In the modern era, in the first half of the 16th century, there appeared a lower tower, which was often not so much a place of imprisonment, but slow death. The 18th century brought significant changes in the nature and function of prisons, which were associated with the incoming ideas of the Enlightenment to the Republic, according to which the penalty was meant to be a means of improvement and rehabilitation rather than retribution. Deposition in the tower, which was a place of repentance devoid of any factors of rehabilitation, was graduały replaced with sending the convicts to prison. Marshal prison should be noted since it stood for changes. It was a modern facility in which the sentenced were kept in very humanitarian as for those times conditions, and their moral advancement was of great interest so as to make sure they would not return on the criminal path. An important role played also the improvement houses and houses of forced labor, the essential aim of which was the improvement of prisoners’ morality and behaviour through work and prayer.